2006
DOI: 10.1111/j.1475-5661.2006.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Suburban life and the boundaries of nature: resilience and rupture in Australian backyard gardens

Abstract: Despite an academic shift from dualistic to hybrid frameworks of culture/nature relations, separationist paradigms of environmental management have great resilience and vernacular appeal. The conditions under which they are reinforced, maintained or ruptured need more detailed attention because of the urgent environmental challenges of a humanly transformed earth. We draw on research in 265 Australian backyard gardens, focusing on two themes where conceptual and material bounding practices intertwine; spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 50 publications
3
94
2
1
Order By: Relevance
“…One such management goal is the creation of new parks using IGS where size and characteristics are suitable. These results are in line with earlier research that found Japanese respondents are overall hesitant to embrace the concept of urban wilderness, a concept that has figured prominently in work on IGS from Europe, North America and Australia [27,28,[39][40][41][42][43][44][45][46][47][48][49][50]. Yet this does not imply that residents do not perceive the value of IGS as a different kind of urban green space.…”
Section: Preferred Management Goalssupporting
confidence: 81%
“…One such management goal is the creation of new parks using IGS where size and characteristics are suitable. These results are in line with earlier research that found Japanese respondents are overall hesitant to embrace the concept of urban wilderness, a concept that has figured prominently in work on IGS from Europe, North America and Australia [27,28,[39][40][41][42][43][44][45][46][47][48][49][50]. Yet this does not imply that residents do not perceive the value of IGS as a different kind of urban green space.…”
Section: Preferred Management Goalssupporting
confidence: 81%
“…In Australia, preference for native plants varied considerably with some householders strongly disliking native plants (Kendal et al 2012). Conservation attitudes tend to be associated with a preference for native plants in gardens (Head andMuir 2006, Zagorski et al 2004), however the householders in our study showed only a weak positive association between proenvironmental orientation and native species richness (van Heezik et al 2013). http://www.ecologyandsociety.org/vol19/iss4/art17/ In another southern temperate city in New Zealand, Stewart et al (2009) found native trees and shrubs were common in private woodland gardens, particularly in the lower height categories, and suggested sites such as these were "hotspots" of native woody diversity.…”
Section: Native Representation In Woody Plant Communitiesmentioning
confidence: 99%
“…For example, five U.S.-based urban foraging studies relied on in-depth interviewing techniques, and three included time spent in direct participant-observation of foraging [12]. Ethnographic methods have been shown to be especially effective in studying everyday interactions between people and nature [14,43] and obtaining an "insider's view" of foraging practices [25].…”
Section: Interviewsmentioning
confidence: 99%